Innate immune cells in vascular lesions: mechanism and significance of diversified immune regulation - Jinjing Wu; Yulu Qian; Kuang Yang; Shuhua Zhang; Erming Zeng; Daya Luo (Annals of Medicine)
Angiogenesis is a complex physiological process. In recent years, the immune regulation of angiogenesis has received increasing attention, and innate immune cells, which are centred on macrophages, are thought to play important roles in vascular neogenesis and development. Various innate immune cells can act on the vasculature through a variety of mechanisms, with commonalities as well as differences and synergistic effects, which are crucial for the progression of vascular lesions. In recent years, monotherapy with antiangiogenic drugs has encountered therapeutic bottlenecks because of the short-term effect of ‘vascular normalization’. The combination treatment of antiangiogenic therapy and immunotherapy breaks the traditional treatment pattern. While it has a remarkable curative effect and survival benefits, it also faces many challenges. This review focuses on innate immune cells and mainly introduces the regulatory mechanisms of monocytes, macrophages, natural killer (NK) cells, dendritic cells (DCs) and neutrophils in vascular lesions. The purpose of this paper was to elucidate the underlying mechanisms of angiogenesis and development and the current research status of innate immune cells in regulating vascular lesions in different states. This review provides a theoretical basis for addressing aberrant angiogenesis in disease processes or finding new antiangiogenic immune targets in inflammation and tumor.